Ameliorative effect of vanillin on scopolamine-induced dementia-like cognitive impairment in a mouse model - Anand, Abhinav; Khurana, Navneet; Ali, Nemat; AlAsmari, Abdullah F.; Alharbi, Metab; Waseem, Mohammad; Sharma, Neha (Frontiers in Neuroscience, 2022)
Background Alzheimer’s disease (AD) is the most common form of dementia which is among the top five causes of death in the United States. It is a neurodegenerative disorder that causes a permanent loss in memory and cognition. The current pharmacotherapy for AD is based on providing symptomatic relief only, with many side effects. There is a need for a safer, disease modifying drug for treatment of AD. Experimental Approach PASS online software was used to screen the phytoconstituents on the basis of their predicted effects on various AD related targets. Vanillin was selected as the compound of interest as it has not been researched upon elaborately in any animal model of AD. Acetylcholinesterase inhibitory activity of vanillin was established in vitro. Thereafter, it was evaluated in exteroceptive memory model and scopolamine induced dementia like cognitive impairment in mice, for its ameliorative effect. Results Vanillin showed acetylcholinesterase inhibitory activity in vitro and the IC50 value was calculated to be 0.033 mM. Vanillin significantly reversed the memory and behavioural deficits caused by scopolamine as demonstrated by significant improvement in memory in negative reinforcement, elevated plus maze and spatial learning paradigms. Vanillin also proved to have nootropic effect. Also, vanillin proved to have significantly better antioxidant and acetylcholinesterase inhibitory effects in vivo than donepezil hydrochloride. Conclusion Our results suggest that vanillin is a safe and effective natural drug candidate having great potential for treatment of AD. However, more research is required to evaluate its effect on Abeta plaques and Tau neurofibrillary tangles, in vivo.